Incidencia de pancreatitis subclínica en caninos (Canis lupus familiaris) alimentados con dietas irregulares, atendidos en la Clínica Veterinaria los Andes. - Altamirano Chiriboga, Lenin (2024)
The purpose of this document is to emphasize the importance of a balanced diet in canines, considering that humans have developed a close relationship with their pets, even influencing their eating habits, adopting the habit of adding food for human consumption to the diet and supplying of supplements that lead to an unbalanced diet, causing health problems such as subclinical pancreatitis. The main objective of this study is to determine the incidence of subclinical pancreatitis in canines fed irregular diets, treated at the Los Andes Veterinary Clinic. For this, the patients who came to the Clinic for vaccinations or control were selected, for two months, after the anamnesis, those who maintained irregular diets, aged between 1 to 7 years, and who manifested various symptoms (vomiting, diarrhea, anorexia, alopecia, pruritus, etc.); 65 pets were selected and underwent TGO and TGP liver profile laboratory tests; pancreatic amylase and lipase profile as well as liver-pancreatic ultrasound. For its part, a survey was applied to the owners of these 65 pets. As a result, an incidence of subclinical pancreatitis was found that reaches 43% of patients with a clear and precise diagnosis, while, presumptively, with diagnostic aids (clinical and ultrasound examinations) and clinical signs it exceeds 55% of patients. The results obtained highlight the importance of knowledge of the diet provided to the pet by the owner, the impact of subclinical pancreatitis on the pet's health status, and the support of medical examinations such as pancreatic ultrasound.